ANALYSIS OF SERVICE QUALITY AND SATISFACTION CUSTOMERS USING THE FUZZY METHOD ON PLASA TELKOM MAJALENGKA - Tia Widianarti; Agus Alamsyah; Whydiantoro Whydiantoro (Jurnal Mekanika dan Manufaktur, 2021)
Plasa Telkom is a service that is fully managed by us or in cooperation with partners is provided to serve the customers / potential customers are serviced directly (face to face) with a wide range of possibilities, both recognize the need for all information related to our services and products for the fulfillment of the product itself. Plasa is a facility walk-in customer service points where customers can obtain a variety of information products and services, including billing, payment, suspension of subscriptions, promotions until the grievance. Among the types of serv phone bill payment, payment of the new post, a new plug / mutation, disorders, and others. Indihome product (phone, internet on fiber or high speed internet and cable useetv). Here the author will discuss about the quality of service on the plaza Telkom Majalengka through fuzzy method. Dimensions that will be discussed is the reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (empathy), and evidence (tangibles). In order to determine each of these dimensions with fuzzy measurement.